2020
DOI: 10.1002/jbmr.3994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Odanacatib on Bone Structure and Quality in Postmenopausal Women With Osteoporosis: 5-Year Data From the Phase 3 Long-Term Odanacatib Fracture Trial (LOFT) and its Extension

Abstract: Odanacatib (ODN), a selective oral inhibitor of cathepsin K, was an investigational agent previously in development for the treatment of osteoporosis. In this analysis, the effects of ODN on bone remodeling/modeling and structure were examined in the randomized, double‐blind, placebo‐controlled, event‐driven, Phase 3, Long‐term Odanacatib Fracture Trial (LOFT; NCT00529373) and planned double‐blind extension in postmenopausal women with osteoporosis. A total of 386 transilial bone biopsies, obtained from consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…In a preclinical model, in ovariectomized rhesus monkeys treated for 21 months, histomorphometric analysis indicate that both osteoclast number and osteoclast surface increased approximately 4‐fold by odanacatib treatment compared to vehicle . Similarly, in the bone biopsy substudy of LOFT, osteoclast surface area at Month 36 was approximately doubled in patients receiving 50 mg weekly odanacatib relative to patients receiving placebo in the histomorphometric analysis of transilial bone biopsies …”
Section: Introductionsupporting
confidence: 72%
“…In a preclinical model, in ovariectomized rhesus monkeys treated for 21 months, histomorphometric analysis indicate that both osteoclast number and osteoclast surface increased approximately 4‐fold by odanacatib treatment compared to vehicle . Similarly, in the bone biopsy substudy of LOFT, osteoclast surface area at Month 36 was approximately doubled in patients receiving 50 mg weekly odanacatib relative to patients receiving placebo in the histomorphometric analysis of transilial bone biopsies …”
Section: Introductionsupporting
confidence: 72%
“…without blocking bone formation [7][8][9], a finding partially upheld by the present study, where histomorphometry showed no significant reduction in EcMAR or PsMAR. Previous work in OVX monkeys has reported increased bone formation on both periosteal and endocortical surfaces in the central femur [40], but we did not see this, suggesting a species difference in the effect of ODN on periosteal bone formation.…”
Section: Cathepsin K Inhibition By Odn Has Been Reported To Suppress supporting
confidence: 56%
“…Odanacatib has received a lot of attention as a potential osteoporosis drug since it inhibits osteoclast activity and function, rather than osteoclast generation, resulting in prevention of bone resorption with more modest overall effects on the ability of osteoblasts to form bone than most other anti-resorptive agents. It still remains unclear whether these effects reflect functional blockade of osteoclast-driven coupling processes or whether CTSK inhibition may have direct effects on CTSK-expressing periosteal mesenchymal progenitors [ 90 , 91 ]. Although odanacatib was highly effective in reducing fractures of postmenopausal women in clinical phase-3, its further development was discontinued due to concerns regarding risk of cerebrovascular events [ 92 ].…”
Section: Impact Of Therapeutic Agents On Osteoblast-osteoclast Intmentioning
confidence: 99%